2016
DOI: 10.1051/matecconf/20164801003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical computation of the main gas-dynamic bearing static characteristics for the ball gyroscope

Abstract: Abstract. The numerical computation questions and analysis of the engineering calculation of the main gas-dynamic bearing static characteristics for the ball gyroscope experimental model are considered. The developed gyroscopic device construction is provided. These investigations for evaluation of the possibility to realize a sensitive element, which base on the developed device were provided. It is supposed, that this sensitive element can be used in information measuring systems of various applications. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The mathematical model is based on solving the system of equations of fundamental laws of mass, momentum, and energy conservation. The system closes the initial and boundary conditions, as well as defining relations [6].…”
Section: Numerical Simulationmentioning
confidence: 77%
See 2 more Smart Citations
“…The mathematical model is based on solving the system of equations of fundamental laws of mass, momentum, and energy conservation. The system closes the initial and boundary conditions, as well as defining relations [6].…”
Section: Numerical Simulationmentioning
confidence: 77%
“…The total layout length is 68 mm and the diameter -77 mm; weight -not more than 1 kg. Dimensions are not the final [6].…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, many scholars have found that the complex structure of high-speed motorized spindles can be simplified and equated into a rotor-bearing system [12] .Therefore, the bearing forces, overall structure and dynamic characteristics all have an impact on the dynamic response of the motorized spindle.There is no doubt that bearings have a very important position in the motorized spindle system. As the main support part of the high-speed motorized spindle, rolling bearings have a great influence on the efficiency and dynamic stability of the motorized spindle [13][14][15][16][17][18] .The research on rolling bearings can be traced back to the earliest decades, during which the mechanical equilibrium model of rolling bearings has gone through the static model, the quasi-static model to the dynamic model [19] .Harris [20] proposed a bearing channel control theory to study the effect of bearing preload on bearing stiffness and internal parameters.The static load carrying capacity and characteristics of the bearings were considered in the development of the gyroscope structure by I.Anastasiya et al [21] . Wang [22] proposed an improved nonlinear dynamic model for angular contact ball bearings considering preload conditions, Hertz contact and lubrication.Zhao [23] analyzed the balance equation of the gyroscopic moment of the rolling element and the relationship between the friction coefficient between the rolling element and the groove for high-speed angular contact ball bearings, and determined the variation law of the friction coefficient required for the balance between the axial force of the gyroscopic moment and the rotational speed.Yi Qin [24] proposed to represent the fault excitation by using B-spline fitting displacement excitation, and the dynamic response was calculated by using the Runge-Kutta method for different fault sizes and rotational speeds.Martynenko et al [25] considers the interconnection of electromagnetic and mechanical control processes, the dynamics of a rotor in a magnetically levitated bearing is studied and experimentally verified.Jiyin Tian [26] developed a dynamic model including thermo-elastohydrodynamic lubrication to simulate the transient process of high-speed angular contact ball bearings by considering the rotational and non-Newtonian effects of TEHL.Dinh Sy Truong et al [27] discusses the influence of thermal effects on angular contact ball bearings in high-speed spindles, and proves experimentally that the thermal effects will have a certain impact on bearing stiffness.…”
Section: Introductionmentioning
confidence: 99%